Meningkatkan Kualitas Pembelajaran di Sekolah Dasar Melalui Kurikulum yang Merdeka (Jurnal Pendidikan Indonesia (JOUPI), 2024)
Education in Indonesia has always been a major concern, given its crucial role in shaping the future generation. However, in recent years, our education system has faced various challenges that require innovation and fundamental change. One of the government's efforts to overcome this is by launching the Independent Curriculum. Through this curriculum, it is hoped that a more meaningful, enjoyable, and relevant learning process can be created to meet the needs of students. Thus, the teaching and learning process can be adjusted to the unique characteristics and needs of each student. The Independent Curriculum also encourages the development of 21st century competencies, such as critical, creative, and collaborative thinking, which are urgently needed in today's digital era, an effort to unleash the potential of students. This study uses qualitative research with a descriptive approach. Because this research is an analytical study and not a calculation, the results obtained are stated in the form of statements obtained from observations of the research object and are factual or in accordance with existing phenomena. The results of this study are Designing interesting and meaningful learning and a challenge that is continuously faced by educators. However, by applying the principles of active learning, differentiated learning, and collaborative learning, teachers can create a fun and inspiring learning environment for students.